2017
DOI: 10.1007/s11010-017-3247-y
|View full text |Cite
|
Sign up to set email alerts
|

Translational regulation in the anoxic turtle, Trachemys scripta elegans

Abstract: The red-eared slider turtle (Trachemys scripta elegans), has developed remarkable adaptive mechanisms for coping with decreased oxygen availability during winter when lakes and ponds become covered with ice. Strategies for enduring anoxia tolerance include an increase in fermentable fuel reserves to support anaerobic glycolysis, the buffering of end products to minimize acidosis, altered expression in crucial survival genes, and strong metabolic rate suppression to minimize ATP-expensive metabolic processes su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The molecular mechanisms that underlie anoxia tolerance adaptations include: post-translational modifications, epigenetic regulation, transcription factor regulation, the accumulation of organic osmolytes, and the post-transcriptional regulation of small regulatory non-coding RNAs called microRNAs (miRNAs) (Szereszewski and Storey, 2018;Wijenayake et al, 2018;Biggar and Storey, 2017;Green and Storey, 2016;Kornfeld et al, 2012;Krivoruchko and Storey, 2010;Muir et al, 2007). miRNAs are highly conserved sequences of non-coding RNA approximately 22 nucleotides long that have been identified as critical regulators of a diverse range of cellular functions through their ability to suppress translation (Lund et al, 2004;Christopher et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms that underlie anoxia tolerance adaptations include: post-translational modifications, epigenetic regulation, transcription factor regulation, the accumulation of organic osmolytes, and the post-transcriptional regulation of small regulatory non-coding RNAs called microRNAs (miRNAs) (Szereszewski and Storey, 2018;Wijenayake et al, 2018;Biggar and Storey, 2017;Green and Storey, 2016;Kornfeld et al, 2012;Krivoruchko and Storey, 2010;Muir et al, 2007). miRNAs are highly conserved sequences of non-coding RNA approximately 22 nucleotides long that have been identified as critical regulators of a diverse range of cellular functions through their ability to suppress translation (Lund et al, 2004;Christopher et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, we and others have identified mTORC1 as a key regulator governing animal survival under various environment-induced situations of metabolic rate depression. These have included hibernation in mammals [ 15 , 16 ], anoxia-tolerance of submerged turtles [ 17 ], hypoxia-tolerance of naked mole rats [ 18 ], and dehydration-induced estivation in frogs [ 19 ]. A surprising finding across these studies is that mTORC1 can be both suppressed and activated during periods of metabolic depression, suggesting that its functional role is stress-type and species-dependent.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…One study measuring de novo protein synthesis in red-eared sliders indicated that the rate of radiolabeled 35 S-methionine incorporation was not substantially reduced after 20 hours of anoxia exposure, and 35 S-methionine was actually elevated in select tissues including the liver and heart [ 69 ]. Biochemical studies have shown that levels of p-Akt (Ser-473) were elevated in the liver and muscle of red-eared slider turtles during anoxia, meanwhile, p-mTOR was maintained at a similar level compared to controls in the liver but increased by ~4.5-fold in the skeletal muscle [ 17 ]. Consistent with mTORC1 being activated during oxygen deprivation, levels of p-S6 protein and p-4E-BP1 were also highly increased in turtles after 20 hours of anoxia exposure [ 17 ].…”
Section: Mtorc1 Control Of Cell Growth Under Metabolic Stressmentioning
confidence: 99%
See 2 more Smart Citations